2014
DOI: 10.4103/0971-4065.132999
|View full text |Cite
|
Sign up to set email alerts
|

Renal histology in diabetic nephropathy: "A novel perspective"

Abstract: Diabetic nephropathy (DN) is the leading cause of end-stage renal disease all over the world. India has a high incidence and prevalence of diabetes and >30% have nephropathy. Recently, a histological classification has been proposed. This study analyzed the renal histology in 114 diabetic patients with renal dysfunction. Nearly 75% of patients had DN. Fifty five (63.95%) were males. Mean duration of diabetes was 7.04 ± 4.9 years. Mean serum creatinine in study group was 5.2 ± 2.9 mg/dl, with mean estimated glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In most of the previous studies, the investigators have found difference in certain parameters between DKD and NDKD, but they have mostly not tested the same in the logistic regression model. [19][20][21] In few studies (retrospective studies of targeted renal biopsies), regression analysis was performed, 22 23 and some even came up with equations 24 25 to predict probability of either DKD or NDKD. However, it is important to appreciate that these equations were of little use for decision making at individual patient level in day-to-day clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the previous studies, the investigators have found difference in certain parameters between DKD and NDKD, but they have mostly not tested the same in the logistic regression model. [19][20][21] In few studies (retrospective studies of targeted renal biopsies), regression analysis was performed, 22 23 and some even came up with equations 24 25 to predict probability of either DKD or NDKD. However, it is important to appreciate that these equations were of little use for decision making at individual patient level in day-to-day clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the previous studies, the investigators have found difference in certain parameters between DKD and NDKD, but they have mostly not tested the same in the logistic regression model 19–21…”
Section: Discussionmentioning
confidence: 99%
“…4 During early stages of diabetic nephropathy, functional and structural abnormalities of glomerular capillaries occur. 5 The nitric oxide (NO) is believed to be involved in the early and late alterations of glomerular hemodynamics due to diabetes. [6][7][8] There are at least three NO-synthases, named neuronal NOS (nNOS), endothelial NOS (eNOS) and inducible NOS (iNOS) that are present within the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical situation simplying non-diabetic renal disease includes shorter duration of diabetes, microscopic hematuria and active urinary sediment in the absence of retinopathy [12]. An Indian study showed a poor correlation between DN and DR in type 2 diabetes mellitus and suggested that renal biopsy is useful in staging the lesions in subjects with diabetes having renal dysfunction [13]. A similar discordance between DR and DN in type 2 diabetes was reported, advocating the requirement of renal biopsy for a precise renal pathological diagnosis in these situations [14].…”
mentioning
confidence: 99%